Politics and the emotions : the affective turn in contemporary political studies - Hoggett, Paul 1951-; Thompson, Simon (Continuum, 2012)
"Politics and the Emotions is a unique collection of essays that reflects the affective turn in the analysis of today's political world. Contributed by both prominent and younger scholars from Europe, US, and Australia, the book aims to advance the debate on the relation between politics and the emotions. To do so, essays are organized around five key thematic areas: emotion, antagonism and deliberation, the politics of fear, the affective dimension of political mobilization, the politics of reparation, and politics and the triumph of the therapeutic. In addition, each chapter includes a case study to demonstrate the application of concepts to practical issues, from the war on terror in the UK and the AIDS activist organization ACT UP in the US to women's liberation movement in New Zealand and Dutch policy experiments. Politics and the Emotions provides an accessible introduction to a rapidly developing field that will appeal to students in political theory, public and social policy, as well as the theory and practice of democracy."--Publisher's website